The Essence of Heaven Adam As in the Qur'an (Study of Wahbah Al-Zuhaili's Interpretation of Heaven in Surah Al-Baqarah Verse 35 in the Book of Al-Tafsir Al-Munir) - Junianto Adinata; Moh. Jufriyadi Sholeh (Values: Jurnal Kajian Islam Multidisiplin, 2025)
The views of scholars and commentators regarding the heaven that Prophet Adam AS once lived in have become an interesting debate, creeping between the religious meanings of the word Al Jannah. Some scholars believe that the heaven of Prophet Adam alaihissalam is in the sky, while others insist that the beauty of heaven is incarnated on the surface of the earth. This dispute aroused a desire in researchers to dig deeper, especially regarding Wahbah Al-Zuhaili's interpretation of the concept of heaven in surah Al-Baqarah Verse 35, which is carefully documented in the Book of Tafsir Al-Munir. Within the framework of this study, at least two aspects will be outlined on which the analysis will focus. The first aspect includes an in-depth interpretation of the nature of heaven in the Qur’an, especially in the perspective put forward by Wahbah Al-Zuhaili. The second aspect will examine the characteristics of the interpretation regarding the nature of heaven that was once occupied by Prophet Adam AS, especially in the context of Tafsir Al-Munir formulated by Wahbah Al-Zuhaili. This research is in the nature of literature (Library Research), and the type of research used is descriptive analysis, which aims to get a complete and clear picture of the problem that the researcher studies, namely the nature of Adam's heaven as in the Qur’an (Study of the interpretation of Wahbah Al-Zuhaili about Heaven in surah Al-Baqarah Verse 35 in the Book of Tafsir Al-Munir). The results of this research mean that Wahbah Al-Zuhaili means that the word al-Jannah is a garden, whereas in surah Al-Baqarah verse 35, the word al-Jannah which is mentioned in the form of ma'rifah cannot be interpreted other than heaven eternity in the sky. And the characteristics of Wahbah Al-Zuhaili's interpretation of the nature of Adam AS's heaven are: Linguistic Approach, Thematic Approach, and Use of Other Sources.